2022
DOI: 10.1101/gr.276363.121
|View full text |Cite
|
Sign up to set email alerts
|

Early embryonic mutations reveal dynamics of somatic and germ cell lineages in mice

Abstract: De novo mutations accumulate with zygotic cell divisions. However, the occurrence of these mutations and the way they are inherited by somatic cells and germ cells remain unclear. Here, we present a novel method to reconstruct cell lineages. We identified mosaic mutations in mice using deep whole-genome sequencing and reconstructed embryonic cell lineages based on the variant allele frequencies of the mutations. The reconstructed trees were confirmed using nuclear transfer experiments and the genotyping of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In summary, we anticipate that our study will guide researchers to the best use of current algorithms. We expect that accurate analysis of mosaic variants will broaden our understanding of fundamental human development, as well as other model organisms 5,31 . Also, for method developers, our study will be a good starting point for technical advances in mosaic variant calling to the germline and somatic variant levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, we anticipate that our study will guide researchers to the best use of current algorithms. We expect that accurate analysis of mosaic variants will broaden our understanding of fundamental human development, as well as other model organisms 5,31 . Also, for method developers, our study will be a good starting point for technical advances in mosaic variant calling to the germline and somatic variant levels.…”
Section: Discussionmentioning
confidence: 99%
“…Postzygotic mutations continuously occur along the zygote-to-adult trajectory, resulting in genetic mosaicism. Recently, the capabilities to examine the mosaic mutations at the genome level have led to a series of discoveries, including the mutational processes and landscapes involved in the development [1][2][3] and aging 4 of human and nonhuman organisms 5 , the causes of neurological disorders 6 and cancer predispositions 7 . As research questions are being answered, growing attention and demand are required for the complete investigation of mosaicism, warranted by the accurate detection of mosaic mutations.…”
mentioning
confidence: 99%
“…The Nell2 SNV, an early embryogenic SNV mutation identified in this study, was expanded massively in hematopoietic cells; however, when this expansion occurred remains unknown. We recently developed a method for reconstructing early embryonic cell lineages using spontaneous de novo mutations that are detected directly using deep-coverage whole-genome sequencing of adult tissues to reconstruct the lineages based on the relationship of VAFs between mosaic mutations 36 . Using this method, we revealed that one spontaneous mutation occurs per cell division in early mouse embryos (before gastrulation) and that its distribution varies between embryonic tissues after gastrulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, de novo genetic mutations accumulate even with the first zygotic cell divisions [208], so in-womb development represents a "sensitive window" for the introduction of mutations because of a higher rate of cellular proliferation [209]. A human cell must repair over 10,000 DNA lesions per day to counteract the intrinsic causes of DNA damage, but it is also necessary to consider the lesions induced by environmental sources of DNA damage [210].…”
Section: Breast Cancer Disparities Related To Developmental Disordersmentioning
confidence: 99%